"And BAM. You Have a Connection”: Blind/Partially Blind Students and the Belonging in Academia Model - Bulk, Laura Yvonne; Jarus, Tal; Nimmon, Laura (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
Blind/partially blind people are underrepresented in post-secondary education and lack equitable opportunities to develop a sense of belonging. This study shares narratives of 28 blind/partially blind students from across Turtle Island (in what is colonially called Canada) using Teng et al.’s (2020) Belonging in Academia Model (BAM) as a conceptual framework. Thematically analyzed findings suggest blind/partially blind students’ perspectives offer nuance to the BAM’s conceptualization of how belonging develops through affiliation, familiarity, acceptance, interdependent relationships, and sense of equity. Based on blind/partially blind perspectives, the former trusting connections dimension was renamed interdependent relationships. By attending to the underrepresented perspectives of blind/partially blind students, stakeholders can become more responsive to the experiences of people from equity-deserving groups. Understanding facilitators and barriers to belonging could result in culturally safer and more inclusive pedagogical practices. Only when we create spaces where everyone can belong will higher education move toward being more just.